2017
DOI: 10.1007/s00068-017-0788-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of anterior ring fixation of the ramus in type C pelvis fractures

Abstract: The bicortical, fully threaded 6.5-mm pubic ramus screw was the only anterior fixation construct tested that controlled motion at both the anterior and posterior pelvic rings in the absence of posterior fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Firstly, the insertion of a cannulated screw in this area is difficult and dangerous. McLachlin et al [ 4 ] declared that the diameter of a cannulated screw must be no <4.5 mm and penetrate the bilateral cortexes of the pubis to obtain the same stability as a reconstruction plate in the treatment of pubic fractures. These requirements are attainable in the treatment of superior pubic ramus fractures, which are medial to the obturator, because the screw length can be short and the operation can performed under direct vision to ensure the correct location of the screw and avoid damage to important nerve and vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firstly, the insertion of a cannulated screw in this area is difficult and dangerous. McLachlin et al [ 4 ] declared that the diameter of a cannulated screw must be no <4.5 mm and penetrate the bilateral cortexes of the pubis to obtain the same stability as a reconstruction plate in the treatment of pubic fractures. These requirements are attainable in the treatment of superior pubic ramus fractures, which are medial to the obturator, because the screw length can be short and the operation can performed under direct vision to ensure the correct location of the screw and avoid damage to important nerve and vessels.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing number of studies have shown that ignorance of instability or excessive displacement of anterior ring fractures could increase the chance of nonunion, lead to long-term pain with limited mobility and result in severe complications, such as deep vein thrombosis, decubitus, or muscle dystrophy. [ 4 – 6 ] Some mechanical tests have demonstrated that fixation of both anterior and posterior ring can bring greater stability of the pelvis and had better prognosis than simple posterior ring fixation in Tile C pelvic fractures. [ 2 , 4 ] Therefore, anterior ring injury in Tile C fracture is now an absolute indication for surgical management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher postoperative stability is an important advantage: it protects against implant loosening or failure and secondary fracture displacement. McLachlin et al tested four different anterior pelvic fixation methods in a vertically unstable pelvic fracture without posterior fixation [5]. The bicortical, fully threaded 6.5 mm retrograde transpubic screw provided the highest stability with the smallest displacement in the anterior and posterior pelvic ring.…”
mentioning
confidence: 99%